Antimicrobial susceptibility surveillance and antimicrobial resistance in Neisseria gonorrhoeae in Africa from 2001 to 2020: A mini-review - Kakooza, Francis; Kiggundu, Reuben; Mboowa, Gerald; Kateete, Patrick David; Nsangi, Olga Tendo; Kabahita, Jupiter Marina; Ssentalo Bagaya, Bernard; Golparian, Daniel; Unemo, Magnus (Frontiers in Microbiology, 2023)
Antimicrobial resistance (AMR) in Neisseria gonorrhoeae (NG), compromising gonorrhea treatment, is a global public health concern. Improved, quality-assured NG AMR monitoring at the global level is essential. This mini-review examined NG AMR susceptibility surveillance and AMR data from the African continent, 2001-2020. Eligible peer-reviewed publications (n=30) containing NG AMR data for antimicrobials currently recommended for gonorrhea treatment were included. Overall, very limited NG surveillance and AMR data was available. Furthermore, the NG AMR surveillance studies varied greatly regarding surveillance protocols (e.g., populations and samples tested, sample size, antimicrobials examined), methodologies (e.g., antimicrobial susceptibility testing method [agar dilution, minimum inhibitory concentration (MIC) gradient strip test, disc diffusion test] and interpretative criteria), and quality assurance (internal quality controls, external quality assessments [EQA], and verification of AMR detected). Moreover, most studies examined a suboptimal number of NG isolates, i.e., less than the WHO Global Gonococcal Antimicrobial Surveillance Program (GASP) and WHO Enhanced GASP (EGASP) recommendations of ≥100 isolates per setting and year. The notable inter-study variability and frequently small sample sizes make appropriate inter-study and inter-country comparisons of AMR data difficult. In conclusion, it is imperative to establish an enhanced, standardized and quality-assured NG AMR surveillance, ideally including patient metadata and genome sequencing as in WHO EGASP, in Africa, the region with the highest gonorrhea incidence globally. This will enable the monitoring of AMR trends, detection of emerging AMR, and timely refinements of national and international gonorrhea treatment guidelines. To achieve this aim, national and international leadership, political and financial commitments are imperative.